Religion, Ethics and Public Education- Religion, Ethik und öffentliche Bildung- Religia, etyka i edukacja publiczna : With Assistance of Michał Czapara- Unter Mitarbeit von Michał Czapara - Przy współpracy Michała Czapary - Aleksandrowicz, Dariusz (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2012)
Irrespective of the separation between religion and state, societies are confronted with claims to incorporate religious beliefs in public education. The anthology deals with the relevant issues referring to the history of ideas, epistemology, ethics, jurisprudence, political philosophy, and the philosophy of education.Trotz der Trennung zwischen Religion und Staat sind Gesellschaften mit der Forderung konfrontiert, Religion in die öffentliche Bildung zu integrieren. Der Sammelband befasst sich mit einschlägigen Fragen aus dem Bereich der Ideengeschichte, Erkenntnislehre, Ethik, Jurisprudenz, der politischen Philosophie sowie Bildungsphilosophie.Niezaleznie od separacji religii i panstwa spoleczenstwa konfrontowane sa z aspiracjami do wlaczenia religii do systemu edukacji publicznej. Ksiazka podejmuje odnosne problemy w kontescie historii idei, epistemologii, etyki, filozofii prawa, polityki oraz wychowania- Resumé vydavatele
Keywords: filozofie výchovy; religionistika; náboženství; vzdělávání; etika; náboženské vzdělávání; philosophy of education; religious science; religion; education; ethics; religious education; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences